Design and Development of Data Management System to Support The Preparation Process of Accreditation form for Program Study - Artin Finalita; Ervina Ahyudanari (Institut Teknologi Sepuluh Nopember, 2020)
In order to realize public accountability, the program study must actively build an internal quality assurance system. To prove that the internal quality assurance system has been implemented properly and correctly, the program study must be accredited by an external quality assurance institution. Criteria for evaluating commitments in accreditation are outlined in number of standards and are presented by programs study in instruments of forms. The problem that arises is that data/ documents for the process of supporting accreditation forms are not all available in the Program Study so they still have to involve other units to obtain them. The purpose of this study is to design a data management system to prepare the availability of data / documents to support the process of preparing accreditation forms. The System Development Life Cycle (SDLC) method is used with the waterfall model in designing this system. This research has produced an application system called Dokumen Akreditasi Online which is oriented towards standards of accreditation form. Overall the results of testing the system functionality shows that all features in the application can be run. The results of measuring the level of user satisfaction amounted to 75.27% which means that users are satisfied with this system. Thus, the need to prepare for accreditation is faster and easier and useful for other administrative needs.